A splitting brain: Imbalanced neural networks in schizophrenia. Issue 2 (30th May 2015) - Li, Mingli; Deng, Wei; He, Zongling; Wang, Qiang; Huang, Chaohua; Jiang, Lijun; Gong, Qiyong; Ziedonis, Doug M.; King, Jean A.; Ma, Xiaohong; Zhang, Nanyin; Li, Tao
Abstract: Dysconnectivity between key brain systems has been hypothesized to underlie the pathophysiology of schizophrenia. The present study examined the pattern of functional dysconnectivity across whole-brain neural networks in 121 first-episode, treatment-naïve patients with schizophrenia by using resting-state functional magnetic resonance imaging (rsfMRI). Group independent component analysis (ICA) was first applied to rsfMRI data to extract 90 functional components of the brain. The functional connectivity between these ICA components was then evaluated and compared between the patient and control groups. To examine the functional roles of significantly altered between-component connections in patients, each ICA component was ascribed to one of 10 previously well-defined brain networks/areas. Relative to findings in healthy controls ( n =103), 29 altered functional connections including 19 connections with increased connectivity and 10 connections with decreased connectivity in schizophrenia patients were found. Increased connectivity was mainly within the default mode network (DMN) and between the DMN and cognitive networks, whereas decreased connectivity was predominantly associated with sensory networks. Given the key roles of the DMN in internal mental processes and sensory networks in inputs from the external environment, these patterns of altered brain network connectivity could suggest imbalanced neural processing of internal and external information in schizophrenia. Highlights: A large sample of first-episode drug-naïve schizophrenic patients was acquired. Increased connectivity within default-mode network was observed in schizophrenia. Hypoconnectivity was predominantly associated with sensory networks in patients.